Hard carbon-graphene composite modified battery negative electrode and preparation method thereof
Patent Information
- Application Number
- CN202610463320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-23
AI Technical Summary
但单一的碳材料往往效果有限
1、硬碳高比表面积能够吸附硫酸根离子,缓冲充放电过程中的负极体积膨胀与收缩,石墨烯能够构建连续导电网络,大幅加快PbSO4向Pb的转化动力学,两者协同下,从根源上阻止大尺寸、难还原硫酸铅晶体生成,显著延缓电池失效,同时硬碳-石墨烯复合添加剂能够显著提高负极比表面积与电子导电性,改善充电接受能力,将70%DOD 循环寿命由传统电池约800次提升至4000 次以上,并且加入硬碳-石墨烯复合添加剂的负极板结构更稳定,耐深度充放电、耐动态工况冲击;
Smart Images

Figure CN122968253A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and particularly relates to a hard carbon-graphene composite modified battery negative electrode, and a method for preparing the hard carbon-graphene composite modified battery negative electrode. Background Technology
[0002] Lead-acid batteries are widely used in energy storage, communication base stations, construction machinery, and automotive starting applications due to their low cost, high safety, and well-established recycling system. However, under cyclic conditions, the negative electrode of traditional lead-acid batteries is prone to sulfation, leading to the failure of active materials and a sharp decline in cycle life. Furthermore, low temperatures significantly affect battery discharge, limiting their normal use in low-temperature regions.
[0003] In recent years, carbon materials (such as carbon black and graphite) have been widely added to negative electrode lead paste to improve conductivity and suppress sulfation. However, single carbon materials often have limited effects. Graphene has extremely high conductivity and a two-dimensional structure, but pure graphene is prone to agglomeration; hard carbon has abundant amorphous regions and sodium storage properties, but its synergistic effect in lead-acid systems has not been fully explored. Summary of the Invention
[0004] To address the problems in the prior art, the present invention proposes the following technical solution: A hard carbon-graphene composite modified battery negative electrode includes: a negative electrode grid and negative electrode lead paste attached to the negative electrode grid. The negative electrode lead paste comprises, by mass percentage: 90.0%-95.0% lead powder, 0.04%-0.14% short fiber, 0.08%-0.27% humic acid, 0.25%-0.70% barium sulfate, 0.1%-1.0% hard carbon-graphene composite additive, and the balance being deionized water. Sulfuric acid is added to the deionized water in the form of dilute sulfuric acid. The hard carbon-graphene composite additive is composed of hard carbon material and graphene material, and the mass ratio of hard carbon material to graphene material is between 1:2 and 2:1.
[0005] As a preferred embodiment of the above technical solution, the hard carbon material is biomass hard carbon or resin-based hard carbon, and the particle size D of the hard carbon material is... 50 The thickness is 1-10 μm, and the specific surface area of the hard carbon material is greater than 500 m². 2 / g.
[0006] As a preferred embodiment of the above technical solution, the graphene material is multilayer graphene or reduced graphene oxide, the number of layers in the graphene material is less than 10, and the lateral dimension of the graphene material is 5-20 μm.
[0007] 4. The hard carbon-graphene composite modified battery negative electrode according to claim 1, characterized in that the short fiber is polyester short fiber or polypropylene short fiber, and the short fiber length is 1-3 mm.
[0008] A method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery includes the following steps: S1. Hard carbon pretreatment and slurry preparation; Hard carbon material is dispersed in deionized water at a solid-liquid mass ratio of 1:5 to 1:10. 0.3%-1.0% of the hard carbon material mass of a low-boiling-point organic acid, acetic acid, is added and stirred. The organic acid can activate the hard carbon surface through protonation, introducing temporary polar sites to promote subsequent graphene adsorption. Subsequently, 0.5%-2.0% of the hard carbon material mass of a surfactant, propylene glycol methyl ether, is added. After stirring evenly, the mixture is transferred to a ball mill and ball-milled for 1-3 hours to obtain a uniform hard carbon slurry with a solid content of 10%-20%.
[0009] S2, Graphene slurry preparation; Graphene material is dispersed in deionized water at a solid-liquid mass ratio of 1:10-1:20. 0.3%-1.0% of a dispersing agent (isopropanol) by weight of the graphene is added. The dispersing agent is used to reduce the surface tension of the slurry and prevent graphene agglomeration. After stirring evenly, the slurry is ultrasonically treated with an ultrasonic cell disruptor to obtain a stable graphene slurry with a solid content of 5%-10%. S3, Slurry Composite and Interface Optimization; Add the hard carbon slurry to the graphene slurry slowly at a mass ratio of 1:2 to 2:1, stirring constantly until the mixture is uniform. Then, use high-energy ball milling or ultrasonic treatment to uniformly coat the surface of the hard carbon particles with graphene nanosheets to form composite particles. S4. Drying treatment of composite slurry; The composite slurry is dried and then sieved through a 100-200 mesh sieve to obtain a hard carbon-graphene composite additive powder with uniform particle size, excellent dispersibility and no impurity residue. S5, Dry mixing of materials; Weigh out lead powder, short fiber, humic acid, barium sulfate and hard carbon-graphene composite additive by mass percentage and add them to the paste mixer in sequence. Dry mix at low speed for 5-8 minutes until the material is uniform. S6, wet mixing paste of materials; Using a "step-by-step liquid addition" method, first add 5%-8% of the total mass of lead paste to the dry mixture of materials with deionized water, stir at medium speed for 10-15 minutes to fully wet the materials, and then slowly add 3%-6% of the total mass of lead paste with dilute sulfuric acid. Keep the cooling system running throughout the process to control the temperature of the paste to always be below 60℃, and continue stirring for 25-35 minutes. S7, lead paste curing; Add an appropriate amount of deionized water to adjust the consistency of the lead paste. After stirring evenly, let it stand and mature in the paste mixer for 15-20 minutes. Stir evenly again at low speed to obtain a negative electrode lead paste with fine texture and good coating performance. S8. Preparation of composite modified negative electrode bio-plate; The obtained negative electrode lead paste was uniformly coated onto the negative electrode grid, and after curing and drying, a composite modified negative electrode green plate was obtained.
[0010] As a preferred embodiment of the above technical solution, the drying process in step S4 includes spray drying. The composite slurry is fed into the spray dryer at a feed rate of 10-30 mL / min for spray drying. The inlet air temperature of the spray dryer is controlled at 120℃-160℃ and the outlet air temperature is controlled at 60℃-80℃. The high-temperature airflow removes moisture, low-boiling-point organic acids, dispersants and surfactants.
[0011] As a preferred embodiment of the above technical solution, the drying process in step S4 includes spray drying. First, place the composite slurry in a freezer and freeze it at -40℃ to -20℃ for 2-4 hours until it is completely frozen. Then, transfer it to a freeze dryer and dry it at a vacuum of 0.1-10Pa and a sublimation temperature of -20℃ to 0℃ for 12-24 hours. While removing moisture through vacuum sublimation, low-boiling-point organic acids, dispersants and surfactants are also removed.
[0012] As a preferred embodiment of the above technical solution, step S8 includes the following: S8.1 Paste application operation: Select lead-calcium or lead-antimony alloy negative electrode grids. After surface degreasing, rust removal and drying, use mechanical paste application to evenly coat both sides of the grids, control the paste thickness to be uniform, and avoid exposed ribs, missing paste, burrs and edge accumulation. S8.2 Segmented Curing: The coated electrode plates are sent into the curing and drying chamber, and a segmented curing process is adopted: First, keep the lead paste at a temperature of 25℃-30℃ and a relative humidity of 85%-90% for 4-6 hours to allow the moisture on the surface to evaporate slowly and initially form a structural framework. Then, increase the temperature to 45℃-55℃ at a rate of 5-8℃ / h, maintain the humidity at 70%-80%, and cure for 12-16h to promote the formation of stable 3PbO・PbSO4・H2O crystals in the lead paste. Finally, the temperature is reduced to 30℃-35℃ at a rate of 3-5℃ / h, and the relative humidity is reduced to 50%-60%, and maintained for 2-3 hours; then the temperature and humidity are gradually reduced until the electrode plate is fully cured and shaped. S8.3 Drying and Testing: The cured electrode plate is further dried to control the final moisture content of the electrode plate to be no higher than 0.8%. After visual inspection and repair, a negative electrode plate with qualified mechanical strength, firm lead paste bonding and uniform and dense surface is obtained.
[0013] As a preferred embodiment of the above technical solution, the concentration of dilute sulfuric acid in step S6 is 1.15-1.25 g / cm³. 3 The mass fraction of the dilute sulfuric acid is 20% to 30%.
[0014] The beneficial effects of this invention are as follows: 1. Hard carbon's high specific surface area can adsorb sulfate ions, buffering the expansion and contraction of the negative electrode volume during charge and discharge. Graphene can construct a continuous conductive network, significantly accelerating the conversion kinetics of PbSO4 to Pb. The synergy of the two prevents the formation of large-sized, difficult-to-reduce lead sulfate crystals from the source, significantly delaying battery failure. At the same time, the hard carbon-graphene composite additive can significantly improve the specific surface area and electronic conductivity of the negative electrode, improve the charge acceptance capability, and increase the 70% DOD cycle life from about 800 times in traditional batteries to more than 4000 times. Furthermore, the negative electrode plate structure with the addition of hard carbon-graphene composite additive is more stable, resistant to deep charge and discharge, and resistant to dynamic operating conditions. 2. When organic acid dispersants and surfactants are used together as modifying agents, they can effectively activate the hard carbon surface, improve surface hydrophilicity and reactivity, allowing graphene sheets to be more uniformly adsorbed and coated on the hard carbon particles, significantly improving the dispersibility of carbon materials and preventing agglomeration. They can also be completely evaporated and removed along with water during the subsequent drying process, leaving no inorganic or organic impurities in the composite additives, not contaminating the electrolyte, and not affecting the electrochemical performance of the plates. At the same time, they can reduce the viscosity and surface tension of the slurry, improve the process stability of slurry preparation, composite and drying processes, ensure the uniformity and integrity of the hard carbon-graphene composite structure, and maintain the high purity of the battery system, thereby further improving the battery cycle life and low-temperature performance. Attached Figure Description
[0015] Figure 1 The diagram shown is a flowchart of an embodiment; Figure 2 The graph shown is a comparison of the battery life of Example 1, Example 2 and Comparative Example 1 in the 70% DOD cycle life test; Figure 3 The diagram shows a comparison of the low-temperature discharge capacity of the batteries in Example 1, Example 2 and Comparative Example 1 at -20°C. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments and the accompanying drawings.
[0017] A hard carbon-graphene composite modified battery negative electrode includes: a negative electrode grid and negative electrode lead paste attached to the negative electrode grid. The negative electrode lead paste comprises, by mass percentage: 90.0%-95.0% lead powder, 0.04%-0.14% short fiber, 0.08%-0.27% humic acid, 0.25%-0.70% barium sulfate, 0.1%-1.0% hard carbon-graphene composite additive, and the balance being deionized water. Sulfuric acid is added to the deionized water in the form of dilute sulfuric acid. The hard carbon-graphene composite additive is composed of hard carbon material and graphene material, and the mass ratio of hard carbon material to graphene material is between 1:2 and 2:1.
[0018] The hard carbon material is biomass hard carbon or resin-based hard carbon, and the particle size D of the hard carbon material is... 50 The thickness is 1-10 μm, and the specific surface area of the hard carbon material is greater than 500 m². 2 / g.
[0019] The graphene material is multilayer graphene or reduced graphene oxide, the number of graphene layers is less than 10, and the lateral dimension of the graphene material is 5-20 μm.
[0020] The short fibers are polyester short fibers or polypropylene short fibers, and the length of the short fibers is 1-3 mm.
[0021] Hard carbon's high specific surface area can adsorb sulfate ions, buffering the expansion and contraction of the negative electrode volume during charge and discharge. Graphene can construct a continuous conductive network, significantly accelerating the conversion kinetics of PbSO4 to Pb. Together, they fundamentally prevent the formation of large-sized, difficult-to-reduce lead sulfate crystals, significantly delaying battery failure. At the same time, the hard carbon-graphene composite additive can significantly improve the specific surface area and electronic conductivity of the negative electrode, improving charge acceptance and increasing the 70% DOD cycle life from about 800 times in traditional batteries to more than 4000 times. Furthermore, the negative electrode plate structure with the addition of hard carbon-graphene composite additive is more stable, resistant to deep charge and discharge, and resistant to dynamic operating conditions.
[0022] Figures 1-3 The present invention discloses a method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery, comprising the following steps: S1. Hard carbon pretreatment and slurry preparation; Hard carbon material is dispersed in deionized water at a solid-liquid mass ratio of 1:5 to 1:10. 0.3% to 1.0% of the hard carbon material mass of a low-boiling-point organic acid (acetic acid) is added and stirred. The organic acid can activate the hard carbon surface through protonation, introducing temporary polar sites to promote subsequent graphene adsorption. Then, 0.5% to 2.0% of the hard carbon material mass of a surfactant (propylene glycol methyl ether) is added. After stirring until homogeneous, the mixture is transferred to a ball mill and ball-milled at a ball-to-material ratio of 3:1 to 5:1 and a speed of 200 to 400 r / min for 1 to 3 hours to obtain a uniform hard carbon slurry with a solid content of 10% to 20%.
[0023] S2, Graphene slurry preparation; Graphene material is dispersed in deionized water at a solid-liquid mass ratio of 1:10-1:20. 0.3%-1.0% of a dispersing agent (isopropanol) is added by weight of the graphene. The dispersing agent is used to reduce the surface tension of the slurry and prevent graphene agglomeration. After stirring evenly, the slurry is then ultrasonically treated with an ultrasonic cell disruptor at 200-500W power for 20-40 minutes to obtain a stable graphene slurry with a solid content of 5%-10%. S3, Slurry Composite and Interface Optimization; Add the hard carbon slurry to the graphene slurry slowly at a mass ratio of hard carbon to graphene of 1:2-2:1, stirring constantly until the mixture is uniform. Then, use high-energy ball milling (400-600 r / min, 1-2 h) or ultrasonic treatment (300-600 W, 30-50 min) to uniformly coat the surface of the hard carbon particles with graphene nanosheets to form composite particles. S4. Drying treatment of composite slurry; The composite slurry is dried and then sieved through a 100-200 mesh sieve to obtain a hard carbon-graphene composite additive powder with uniform particle size, excellent dispersibility and no impurity residue. S5, Dry mixing of materials; Weigh out lead powder, short fiber, humic acid, barium sulfate and hard carbon-graphene composite additive by mass percentage and add them to the paste mixer in sequence. Dry mix at low speed for 5-8 minutes until the material is uniform. S6, wet mixing paste of materials; Using a "step-by-step liquid addition" method, first add 5%-8% of the total mass of lead paste to the dry mixture of materials with deionized water, stir at medium speed for 10-15 minutes to fully wet the materials, and then slowly add 3%-6% of the total mass of lead paste with dilute sulfuric acid. Keep the cooling system running throughout the process to control the temperature of the paste to always be below 60℃, and continue stirring for 25-35 minutes. S7, lead paste curing; Add an appropriate amount of deionized water to adjust the consistency of the lead paste. After stirring evenly, let it stand and mature in the paste mixer for 15-20 minutes. Stir evenly again at low speed to obtain a negative electrode lead paste with fine texture and good coating performance. S8. Preparation of composite modified negative electrode bio-plate; The obtained negative electrode lead paste was uniformly coated onto the negative electrode grid, and after curing and drying, a composite modified negative electrode green plate was obtained.
[0024] When organic acid dispersants and surfactants are used together as modifying agents, they can effectively activate the hard carbon surface, improve surface hydrophilicity and reactivity, allowing graphene sheets to be more uniformly adsorbed and coated on the hard carbon particles, significantly improving the dispersibility of carbon materials and preventing agglomeration. They can also be completely evaporated and removed along with water during the subsequent drying process, leaving no inorganic or organic impurities in the composite additive, not contaminating the electrolyte, and not affecting the electrochemical performance of the plates. At the same time, they can reduce the viscosity and surface tension of the slurry, improve the process stability of slurry preparation, composite and drying processes, ensure the uniformity and integrity of the hard carbon-graphene composite structure, maintain the high purity of the battery system, and thus further improve the battery cycle life and low-temperature performance.
[0025] The drying process in step S4 includes spray drying. The composite slurry is fed into the spray dryer at a feed rate of 10-30 mL / min for spray drying. The inlet air temperature of the spray dryer is controlled at 120℃-160℃ and the outlet air temperature is controlled at 60℃-80℃. The high-temperature airflow removes moisture, low-boiling-point organic acids, dispersants and surfactants.
[0026] Alternatively, the drying process in step S4 may include spray drying. First, place the composite slurry in a freezer and freeze it at -40℃ to -20℃ for 2-4 hours until it is completely frozen. Then, transfer it to a freeze dryer and dry it at a vacuum of 0.1-10Pa and a sublimation temperature of -20℃ to 0℃ for 12-24 hours. While removing moisture through vacuum sublimation, low-boiling-point organic acids, dispersants and surfactants are also removed.
[0027] Step S8 includes the following: S8.1 Paste application operation: Select lead-calcium or lead-antimony alloy negative electrode grids. After surface degreasing, rust removal and drying, use mechanical paste application to evenly coat both sides of the grids, control the paste thickness to be uniform, and avoid exposed ribs, missing paste, burrs and edge accumulation. S8.2 Segmented Curing: The coated electrode plates are sent into the curing and drying chamber, and a segmented curing process is adopted: First, keep the lead paste at a temperature of 25℃-30℃ and a relative humidity of 85%-90% for 4-6 hours to allow the moisture on the surface to evaporate slowly and initially form a structural framework. Then, increase the temperature to 45℃-55℃ at a rate of 5-8℃ / h, maintain the humidity at 70%-80%, and cure for 12-16h to promote the formation of stable 3PbO・PbSO4・H2O crystals in the lead paste. Finally, the temperature is reduced to 30℃-35℃ at a rate of 3-5℃ / h, and the relative humidity is reduced to 50%-60%, and maintained for 2-3 hours; then the temperature and humidity are gradually reduced until the electrode plate is fully cured and shaped. S8.3 Drying and Testing: The cured electrode plate is further dried to control the final moisture content of the electrode plate to be no higher than 0.8%. After visual inspection and repair, a negative electrode plate with qualified mechanical strength, firm lead paste bonding, and uniform and dense surface is obtained.
[0028] In step S6, the concentration of dilute sulfuric acid is 1.15-1.25 g / cm³. 3 The mass fraction of the dilute sulfuric acid is 20%~30%. Example 1
[0029] Preparation of composite additives: 100 parts of biomass hard carbon with a D50 of 5 μm were added to deionized water and a dispersant, and ball-milled for 2 hours to prepare slurry A. 50 parts of multilayer graphene (sheet diameter approximately 10 μm, number of layers < 8) were added to deionized water and a dispersant, and ultrasonically dispersed for 1 hour to prepare slurry B. Slurries A and B were mixed and ball-milled for another 1 hour to ensure uniform adhesion of graphene to the surface of the hard carbon. Finally, the mixture was spray-dried to obtain hard carbon-graphene composite powder.
[0030] Mixing the paste: Take 1000 parts lead powder, 1 part short fiber, 2 parts humic acid, 5 parts barium sulfate, and 10 parts of the above-mentioned compound additives, and dry mix them in a paste mixer for 3 minutes; then slowly add a paste with a density of 1.4 g / cm³. 3 Add 95 parts of dilute sulfuric acid and an appropriate amount of deionized water, stir for 30 minutes, and control the paste temperature to be below 60℃ to obtain negative electrode lead paste.
[0031] Electrode preparation and assembly: Lead paste is applied to the negative electrode grid, cured and dried, and then assembled with the positive electrode and AGM separator to form a battery. Sulfuric acid electrolyte is injected for formation to obtain the finished battery. Example 2
[0032] The mass ratio of hard carbon to graphene in the composite additive was adjusted to 1:2, and the remaining steps were the same as in Example 1.
[0033] Comparative Example 1 uses a traditional negative electrode formulation, that is, no hard carbon-graphene composite additive is added during paste preparation, only conventional carbon black is added, and the remaining steps are the same as in Example 1.
[0034] Performance testing The batteries prepared in Examples 1-2 and Comparative Example 1 were subjected to cycle life testing (reference standard: cycle test at 70% depth discharge in an environment of 25°C, with the life end point being the capacity decay to 80% of the initial capacity) and low-temperature discharge capacity testing at -20°C. The test results are shown in the table below: Conclusion: The test data shows that the battery using the hard carbon-graphene composite modified negative electrode of this invention has a much longer cycle life than the traditional battery, and its low-temperature performance is also significantly improved.
[0035] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it.
Claims
1. A hard carbon-graphene composite modified negative electrode for a storage battery, characterized in that, include: The negative electrode grid and the negative electrode lead paste attached to the negative electrode grid, wherein the components of the negative electrode lead paste, by mass percentage, include: lead powder 90.0%-95.0%, short fiber 0.04%-0.14%, humic acid 0.08%-0.27%, barium sulfate 0.25%-0.70%, hard carbon-graphene composite additive 0.1%-1.0%, and the balance being deionized water, with sulfuric acid added to the deionized water in the form of dilute sulfuric acid; The hard carbon-graphene composite additive is composed of hard carbon material and graphene material, and the mass ratio of hard carbon material to graphene material is between 1:2 and 2:
1.
2. The hard carbon-graphene composite modified battery negative electrode according to claim 1, characterized in that, The hard carbon material is biomass hard carbon or resin-based hard carbon, and the particle size D of the hard carbon material is... 50 The thickness is 1-10 μm, and the specific surface area of the hard carbon material is greater than 500 m². 2 / g.
3. The hard carbon-graphene composite modified battery negative electrode according to claim 1, characterized in that, The graphene material is multilayer graphene or reduced graphene oxide, the number of graphene layers is less than 10, and the lateral dimension of the graphene material is 5-20 μm.
4. The hard carbon-graphene composite modified negative electrode of a storage battery according to claim 1, characterized in that, The short fibers are polyester short fibers or polypropylene short fibers, and the length of the short fibers is 1-3 mm.
5. A method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Hard carbon pretreatment and slurry preparation; Hard carbon material is dispersed in deionized water at a solid-liquid mass ratio of 1:5 to 1:
10. 0.3%-1.0% of the hard carbon material mass of a low-boiling-point organic acid, acetic acid, is added and stirred. The organic acid can activate the hard carbon surface through protonation, introducing temporary polar sites to promote subsequent graphene adsorption. Subsequently, 0.5%-2.0% of the hard carbon material mass of a surfactant, propylene glycol methyl ether, is added. After stirring evenly, the mixture is transferred to a ball mill and ball-milled for 1-3 hours to obtain a uniform hard carbon slurry with a solid content of 10%-20%. 6.S2, Preparation of graphene slurry; Graphene material is dispersed in deionized water at a solid-liquid mass ratio of 1:10-1:
20. 0.3%-1.0% of a dispersing agent (isopropanol) is added by weight of the graphene. The dispersing agent is used to reduce the surface tension of the slurry and prevent graphene agglomeration. After stirring evenly, the slurry is ultrasonically treated with an ultrasonic cell disruptor to obtain a stable graphene slurry with a solid content of 5%-10%. S3, Slurry Composite and Interface Optimization; Add the hard carbon slurry to the graphene slurry slowly at a mass ratio of 1:2 to 2:1, stirring constantly until the mixture is uniform. Then, use high-energy ball milling or ultrasonic treatment to uniformly coat the surface of the hard carbon particles with graphene nanosheets to form composite particles. S4. Drying treatment of composite slurry; The composite slurry is dried and then sieved through a 100-200 mesh sieve to obtain a hard carbon-graphene composite additive powder with uniform particle size, excellent dispersibility and no impurity residue. S5, Dry mixing of materials; Weigh out lead powder, short fiber, humic acid, barium sulfate and hard carbon-graphene composite additive by mass percentage and add them to the paste mixer in sequence. Dry mix at low speed for 5-8 minutes until the material is uniform. S6, wet mixing paste of materials; Using a "step-by-step liquid addition" method, first add 5%-8% of the total mass of lead paste to the dry mixture of materials with deionized water, stir at medium speed for 10-15 minutes to fully wet the materials, and then slowly add 3%-6% of the total mass of lead paste with dilute sulfuric acid. Keep the cooling system running throughout the process to control the temperature of the paste to always be below 60℃, and continue stirring for 25-35 minutes. S7, lead paste curing; Add an appropriate amount of deionized water to adjust the consistency of the lead paste. After stirring evenly, let it stand and mature in the paste mixer for 15-20 minutes. Stir evenly again at low speed to obtain a negative electrode lead paste with fine texture and good coating performance. S8. Preparation of composite modified negative electrode bio-plate; The obtained negative electrode lead paste was uniformly coated onto the negative electrode grid, and after curing and drying, a composite modified negative electrode green plate was obtained.
7. The method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery according to claim 5, characterized in that, The drying process in step S4 includes spray drying. The composite slurry is fed into the spray dryer at a feed rate of 10-30 mL / min for spray drying. The inlet air temperature of the spray dryer is controlled at 120℃-160℃ and the outlet air temperature is controlled at 60℃-80℃. The high-temperature airflow removes moisture, low-boiling-point organic acids, dispersants and surfactants.
8. The method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery according to claim 5, characterized in that, The drying process in step S4 includes spray drying. First, place the composite slurry in a freezer and freeze it at -40℃ to -20℃ for 2-4 hours until it is completely frozen. Then, transfer it to a freeze dryer and dry it at a vacuum of 0.1-10Pa and a sublimation temperature of -20℃ to 0℃ for 12-24 hours. While removing moisture through vacuum sublimation, low-boiling-point organic acids, dispersants and surfactants are also removed.
9. The method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery according to claim 5, characterized in that, Step S8 includes the following: S8.1 Paste application operation: Select lead-calcium or lead-antimony alloy negative electrode grids. After surface degreasing, rust removal and drying, use mechanical paste application to evenly coat both sides of the grids, control the paste thickness to be uniform, and avoid exposed ribs, missing paste, burrs and edge accumulation. S8.2 Segmented Curing: The coated electrode plates are sent into the curing and drying chamber, and a segmented curing process is adopted: First, keep the lead paste at a temperature of 25℃-30℃ and a relative humidity of 85%-90% for 4-6 hours to allow the moisture on the surface to evaporate slowly and initially form a structural framework. Then, increase the temperature to 45℃-55℃ at a rate of 5-8℃ / h, maintain the humidity at 70%-80%, and cure for 12-16h to promote the formation of stable 3PbO・PbSO4・H2O crystals in the lead paste. Finally, the temperature is reduced to 30℃-35℃ at a rate of 3-5℃ / h, and the relative humidity is reduced to 50%-60%, and maintained for 2-3 hours; then the temperature and humidity are gradually reduced until the electrode plate is fully cured and shaped. S8.3 Drying and Testing: The cured electrode plate is further dried to control the final moisture content of the electrode plate to be no higher than 0.8%. After visual inspection and repair, a negative electrode plate with qualified mechanical strength, firm lead paste bonding and uniform and dense surface is obtained.
10. The method for preparing a hard carbon-graphene composite modified negative electrode for a storage battery according to claim 5, characterized in that, In step S6, the concentration of dilute sulfuric acid is 1.15-1.25 g / cm³. 3 The mass fraction of the dilute sulfuric acid is 20% to 30%.